Comprehensive characterization of FBXW7 mutational and clinicopathological profiles in human colorectal cancers - Liu, Yiping; Chen, Hanlin; Bao, Hua; Zhang, Jinfeng; Wu, Runda; Zhu, Lingjun (Frontiers in Oncology, 2023)
Background FBXW7 is recognized as a critical tumor suppressor gene and a component of the ubiquitin-proteasome system, mediating the degradation of multiple oncogenic proteins, including c-MYC, Cyclin E, c-Jun, Notch, p53. Around 16% of colorectal cancer (CRC) patients carried FBXW7 somatic mutations, while a comprehensive characterization of FBXW7 somatic mutations in CRC is still lacking. Methods Colorectal cancer patients with tumor samples and matching white blood cell samples in the past five years were screened and DNA sequenced. DNA sequencing data of MSK MetTropism cohort and RNA sequencing data of TCGA COAD cohort were analyzed. Results We discovered that the FBXW7 mutations were associated with higher tumor mutation burden (TMB), higher microsatellite instability (MSI) score, and lower chromosomal instability (CIN) score. Patients with FBXW7 mutations showed better overall survival (HR: 0.67; 95%CI: 0.55-0.80, P < 0.001). However, FBXW7 R465C mutation displayed worse overall survival when compared with other FBXW7 mutations (HR: 1.6; 95%CI: 1.13-3.1, P = 0.015), and with all other mutations (HR: 1.87; 95%CI: 0.99-2.5, P = 0.053). Moreover, in MSI patients, the FBXW7 mutated group showed higher M1 macrophage, CD8+ T cell, and regulatory T cell (Tregs) infiltration rates, and significant enrichment of multiple immune-related gene sets, including interferon-gamma response, interferon-alpha response, IL6 JAK STAT3 signaling, p53 pathway. Conclusions This analysis comprehensively identified FBXW7 alterations in colorectal cancer patients and uncovered the molecular, clinicopathological, and immune-related patterns of FBXW7-altered CRC patients.